Return on influence : the revolutionary power of Klout, social scoring, and influence marketing - Schaefer, Mark (McGraw-Hill, 2012)
Filled with fascinating case studies; interviews; and insider advice; this essential guide explores how brands are identifying and leveraging the worlds most powerful bloggers; tweeters; and YouTube celebrities to build product awareness; brand buzz; and new sales. --